Tsunami Mitigation in a Collaborative Planning Approach and Philosophy of Science Perspectives - Lazarus Ramandei (Yayasan Banu Haji Samsudin, 2026)
This research aims to examine tsunami mitigation using a collaborative approach, particularly at the local level. The main focus is to understand how collaboration between various stakeholders can improve the effectiveness of tsunami mitigation in areas with tsunami potential. The theoretical framework of this research is based on the theories of collaboration and disaster management. Collaboration theory (ontology) explains the importance of cooperation between various parties, including government, communities and non-governmental organizations, in dealing with disasters. The epistemology of this research focuses on how knowledge about disaster mitigation can be acquired and applied through a collaborative approach. This research uses a qualitative method with a case study approach. Data was collected through in-depth interviews with stakeholders at the local level, including local government officials, community members, and representatives of non-governmental organizations. Data analysis was conducted using thematic analysis techniques to identify key themes that emerged from the data. The results show that a collaborative approach to tsunami mitigation has several advantages, including improved coordination among stakeholders, increased community awareness of tsunami risks, and improved local capacity in dealing with disasters. However, the study also found some challenges, such as a lack of resources and support from the central government, as well as a lack of community awareness and participation. The implication of this study is that a collaborative approach can be an effective strategy in tsunami mitigation, especially in areas with tsunami potential. The research also provides recommendations for government and non-government organizations to improve collaboration and coordination in disaster management. This research makes a significant contribution to the literature on disaster mitigation with a focus on collaborative approaches at the local level. The originality of this research lies in its focus which is rarely discussed in the literature, namely the importance of collaboration between various stakeholders in tsunami mitigation. Abstract: This research aims to examine tsunami mitigation using a collaborative approach, particularly at the local level. The main focus is to understand how collaboration between various stakeholders can improve the effectiveness of tsunami mitigation in areas with tsunami potential. The theoretical framework of this research is based on the theories of collaboration and disaster management. Collaboration theory (ontology) explains the importance of cooperation between various parties, including government, communities and non-governmental organizations, in dealing with disasters. The epistemology of this research focuses on how knowledge about disaster mitigation can be acquired and applied through a collaborative approach. This research uses a qualitative method with a case study approach. Data was collected through in-depth interviews with stakeholders at the local level, including local government officials, community members, and representatives of non-governmental organizations. Data analysis was conducted using thematic analysis techniques to identify key themes that emerged from the data. The results show that a collaborative approach to tsunami mitigation has several advantages, including improved coordination among stakeholders, increased community awareness of tsunami risks, and improved local capacity in dealing with disasters. However, the study also found some challenges, such as a lack of resources and support from the central government, as well as a lack of community awareness and participation. The implication of this study is that a collaborative approach can be an effective strategy in tsunami mitigation, especially in areas with tsunami potential. The research also provides recommendations for government and non-government organizations to improve collaboration and coordination in disaster management. This research makes a significant contribution to the literature on disaster mitigation with a focus on collaborative approaches at the local level. The originality of this research lies in its focus which is rarely discussed in the literature, namely the importance of collaboration between various stakeholders in tsunami mitigation. The results show that a collaborative approach to tsunami mitigation has several advantages, including improved coordination among stakeholders, increased community awareness of tsunami risks, and improved local capacity in dealing with disasters. However, the study also found some challenges, such as a lack of resources and support from the central government, as well as a lack of community awareness and participation.The implication of this study is that a collaborative approach can be an effective strategy in tsunami mitigation, especially in areas with tsunami potential. The research also provides recommendations for government and non-government organizations to improve collaboration and coordination in disaster management. This research makes a significant contribution to the literature on disaster mitigation with a focus on collaborative approaches at the local level. The originality of this research lies in its focus which is rarely discussed in the literature, namely the importance of collaboration between various stakeholders in tsunami mitigation.